The epidemiology of amoebiasis in the Northern Territory of Australia over 20 years (2005 – 2024) - Balasubramanya, Bhavya; Dyke, Hayley; Lynar, Sarah; Lomas, Kelly; McMahon, Kimberley; Krause, Vicki; Draper, Anthony (Communicable Diseases Intelligence, 2025)
Amoebiasis is an important parasitic cause of morbidity and mortality worldwide and is known to be endemic in Northern Australia. The Northern Territory is the only jurisdiction in Australia where amoebiasis is notifiable. The epidemiology of amoebiasis across Australia is not well described. We undertook this retrospective study to describe the epidemiology of amoebiasis in the Northern Territory from 1 January 2005 to 30 June 2024. Data were obtained from the Northern Territory Notifiable Disease System. Of the 26 cases identified, most were men (81%), non-Indigenous (88%) and with infection overseas acquired (69%). Most had extra-intestinal manifestations (65%), and most required hospitalisation (54%). There was one death related to amoebic splenic abscess. Of the seven locally acquired cases, all resided in the Top End and Katherine regions, and two were children. The highest annual incidence occurred in 2024, all of whom were returned travellers. This study highlights that amoebiasis in the Northern Territory is both endemic and overseas acquired, and that clinicians should consider this differential diagnosis in people presenting with gastrointestinal symptoms and initiate timely testing and appropriate treatment.